2020
DOI: 10.1088/1742-6596/1491/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Energy Cohesive Calculation for Some Pure Metals Using the Lennard-Jones Potential in Lammps Molecular Dynamics

Abstract: It has been determined by molecular dynamics simulation method the parameter potentials ( ε, σ ) of the Lennard-Jones potential based on the cohesive energy value for some pure metals. The LAMMPS molecular dynamics software was used to simulate and calculate the cohesive energy of the metals. To determine the best value of ( ε, σ ) we verified all calculations using the available experimental data of cohesive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The EAM potential can be quite safely applied for atomistic simulations of metals such as epitaxial film structure and extended defect cores in which correct energies and stability of different atomic configurations are of prime importance for obtaining credible results [47]. To account Cu-C, Cu-Mo, Cu-S, and Cu-C interactions, the 12-6 Lennard-Jones (LJ) potential containing parameters such as the equilibrium distance (σ), the well depth (ε), and LJ cut-offs radius r c = 2.5σ has been used [1,[49][50][51]. The obtained results of collision cascade simulations in vanadium-graphene NC confirm that the LJ potential is an effective potential to use in simulations of collision cascades in NCs [2].…”
Section: Simulation Methodologies 21 Single Cascade In Ncsmentioning
confidence: 99%
“…The EAM potential can be quite safely applied for atomistic simulations of metals such as epitaxial film structure and extended defect cores in which correct energies and stability of different atomic configurations are of prime importance for obtaining credible results [47]. To account Cu-C, Cu-Mo, Cu-S, and Cu-C interactions, the 12-6 Lennard-Jones (LJ) potential containing parameters such as the equilibrium distance (σ), the well depth (ε), and LJ cut-offs radius r c = 2.5σ has been used [1,[49][50][51]. The obtained results of collision cascade simulations in vanadium-graphene NC confirm that the LJ potential is an effective potential to use in simulations of collision cascades in NCs [2].…”
Section: Simulation Methodologies 21 Single Cascade In Ncsmentioning
confidence: 99%
“…Many studies have shown that these alloys participate in the damage cascade processes by which a considerable amount of information-the generation, distribution, and evolution of defects-is acquired in the mechanism of radiation resistance [49][50][51][52][53]. The defect clusters (vacancy clusters and interstitial clusters) become independent individuals for Ni-containing HEAs that play a vital role in inhibiting swelling [22,24,35,37,44,50].…”
Section: Introductionmentioning
confidence: 99%